HETERO-STEREOTYPE DALAM FILM SERI EMILY IN PARIS SEASON 1 - Satiakemala, Silvi; Agustina, Dian (Universitas Hasanuddin, 2024)
This research aims to describe the hetero-stereotypes that appear in the film series